RAED: Response Analysis of Educational Data for leveraging knowledge dissemination system - Olanrewaju, Rashidah Funke; Khan, Burhan Ul Islam; Mir, Roohie Naaz; Baba, Asifa Mehraj; Gannie, Mohammad Rafiq (IEEE, 2015)
The present and future educational system will have 360-degree dependencies on its digitized materials. There has been tremendous approach from every corner of the society including government agencies in every country to implement certain global standards of the educational system, which is going to be completely online. The characteristics of generated data act in agreement with all the parameters of big data such as volume, velocity, veracity, etc. The existing frameworks mainly Hadoop and its ecosystem provide a basic structure to store process and analyze, but it lags the insight to meet the provisioned or conceptualized applications towards enhancing the teaching-learning philosophy. This paper illustrates architecture to handle which latches into the existing framework and its eco-systems. The proposed architecture provides future researchers to validate their algorithm and get the provisioned output for the teaching-learning added for intelligent applications Keywords; Educational Data, Big Data, Data Analytics, Data Mining, Knowledge Discovery